The many challenges of dementia care in Malaysia - Loh, Ken Joey; Ng, Alvin Lai Oon *; Elil, Renganathan *; Chia, Yook Chin *; Lee, Wan Ling; Devi, Mohan (Star Media Group Berhad, 2023)
SEPTEMBER is World Alzheimer’s Month. The theme for this year, “Never too early, never too late”, emphasises risk reduction actions to prevent dementia as well as to delay its progress.